Limit state design of soil slopes - Sam, Man Keong. (2009)
There are a number of different methods of soil slope stability analysis proposed by various researchers. Most of these are limit equilibrium methods, e.g. Bishop's simplified Method of Slices. However, the present trend in most codes, e.g. the draft Eurocode 7 (1992), is to adopt the limit state design (LSD) approach.